Dynamics of twin bubbles formed by ultrasonic cavitation in a liquid - Jinfu Liang (Elsevier, 2021)
Based on potential flow and perturbation theory, a theoretical model is derived to describe the pulsation, translation, and deformation of twin bubbles in an ultrasound field. The amplitudes of radial oscillation, translation, and deformation of twin bubbles are found to depend on initial translation velocities. The radii, translation, and deformation of twin bubbles also exhibit periodic behavior. As the initial translation velocities increase, the periods of two bubbles’ oscillations reduce, and the instable area in the phase space of R01-R02 enlarges because of the interaction between bubbles.